Dietary supplementation with mango leaf powder influences broiler chickens’ growth characteristics, blood parameters, and carcass - Olugbenga David Oloruntola; Samuel Adebowale Adeyeye; Olumuyiwa Joseph Olarotimi; Victor Olabisi Akinduro; Olufemi Adesanya Adu; Francis Ayodeji Gbore; Ojurereoluwa Adebimpe Ayodele (Acta Scientiarum. Animal Sciences, 2024)
This study examined the impact of mango leaf powder supplementation on broiler chickens’ growth, blood parameters, and carcass of broiler chickens. Two hundred (200) day-old broilers were divided into four groups: Control (CONT), 200 mg kg-1 Vitamin C (VITC), 250 mg kg-1 mango leaf powder (MLP2), and 500 mg kg-1 mango leaf powder (MLP3). VITC, MLP2, and MLP3 groups showed significantly higher (p < 0.05) body weight gain than CONT, with similar feed intake and conversion ratios (p > 0.05). Organ weights (heart, lung, liver, spleen) were unaffected (p > 0.05), except for the pancreas in MLP2, which was lower (p < 0.05) than CONT. Hematological indices exhibited no significant differences (p > 0.05). Serum total protein, aspartate aminotransferase, alanine aminotransferase, cholesterol, and creatinine remained stable (p > 0.05). However, serum catalase, glutathione peroxidase, and lipid peroxidase levels were significantly (p < 0.05) increased with mango leaf powder supplementation. Mango leaf powder supplementation improved body weight gain, dressed percentage, and oxidative status of broiler chickens.